An analysis of the managerial performance of Italian museums using a generalised conditional efficiency model. (December 2020) - Guccio, Calogero; Martorana, Marco; Mazza, Isidoro; Pignataro, Giacomo; Rizzo, Ilde
Abstract: Museums are important cultural institutions having the mission of conserving, interpreting, researching and displaying heritage. The evaluation of their efficiency has been extensively investigated in the literature using different approaches and methods. In this paper, we employ a generalised conditional efficiency model to assess the true efficiency of Italian museums, i.e. the efficiency in the provision of museums' service potential, consistently dealing with the impact of the socio-demographic and institutional environment in which museums operate. Results show that the operational environment matters. In particular, conditional estimates suggest that higher income levels and larger hospitality sectors positively influence museums efficiency. Ownership matters: museums' service potential is higher for private institutions while, among public institutions, efficiency is generally lower for state-owned museums. Highlights: Generalised conditional efficiency model measures the technical efficiency of museums. We focus on outputs under the direct control of museums' managers, the so-called service potential. We use a generalised conditional efficiency model to assess the efficiency of a large sample of Italian museums. Results show that both institutional features and operational environment matter for assessment museums' service potential.